Asynchronous Online Tutorial and What Lies Within: A Study in the Listening Course of Universitas Terbuka - Siti Hadianti (JELLT (Journal of English Language and Language Teaching), 2022)
Online tutorial (Tuton) in Universitas Terbuka works asynchronously and can be used by students to support their learning activities anywhere, with a flexible time. Listening is one of the language skills that can be learned through this service. However, studying this subject through an asynchronous online platform is rather challenging. This research investigated students' perspectives on attending listening classes in an asynchronous Tuton mode. The study, which was carried out with a qualitative research approach, was conducted in the semester 2022.1. The number of participants was 21 students of the English Education Department, Faculty of Education and Teacher Training who enrolled in the Listening II (PBIS4220) course. Data was gathered through an open-ended online questionnaire distributed to students. The findings revealed that there are advantages, such as flexibility, interaction and participation, and assessment which can be considered as benefits of the use of asynchronous Tuton. Meanwhile, in terms of challenges, there are also materials and facilities, and feedback that needs to be taken into account. It can be concluded that there are two major findings regarding students’ perspectives of asynchronous online tutorials.